CHANGING ROLE OF INTERCULTURAL COMMUNICATIONS IN THE PROCESS OF RUSSIAN REVOLUTIONARY AND POST-REVOLUTIONARY TRANSFORMATIONS - S. A. Kolobova (Концепт: философия, религия, культура, 2017)
In the article the problems of formation and development of intercultural communication, taking into account the factor of the Russian revolutionary and post-revolutionary turmoil of 1917 are analyzed. The relevance of the research topic is due to the special importance of the system of intercultural and political communication in the condition of bifurcation of the society. The October revolution of 1917 radically changed the world. Exactly at critical stages of development of any country, including Russia, understanding communication participants of different national cultures is the key to stability and creates conditions for the preservation of the public consciousness of the people, its mentality, national character, lifestyle, traditions, system of values. Revolutionary and post-revolutionary society is characterized by the emergence of various socio-cultural conflicts, the resolution of which requires serious efforts from all participants of communication, and its effectiveness becomes a question of survival of the state itself. The degree of elaboration of these issues in Russian and foreign scientific literature is quite high, but the problem in the narrative and theoretical interpretation of semantic characteristics still exists. The objective of the article is the replacement of the lack of scientific justification the evolving role of intercultural communication in specific circumstances complex of the Russian revolutionary and post-revolutionary transformations. The conceptual basis for the research is a comprehensive cognitive-historical explanation of the dynamics of intercultural interaction in Russia caused by the October revolution of 1917 and the subsequent events that define the essence of the transformation of the circumstances, cultural and communicative properties. Thus to define the characteristics of the development of intercultural communication caused by the revolutionary and post-revolutionary actions, is particularly important for modern political science.